Case Report: Systemic treatment for breast and vulvar metastases from resected rectal signet ring cell carcinoma - Han, Yihui; Yang, Wenming; Ma, Qin; Cai, Zhaolun; Yang, Yun; Gou, Junhe; Yuan, Tao; Zhang, Mingming; Zhang, Bo (Frontiers in Oncology, 2023)
Background: Breast and vulvar metastases from rectal signet ring cell carcinoma (SRCC) represent a rare and obscure clinical entity associated with poor survival. Managing patients with metastatic rectal SRCC is extremely challenging due to the absence of high-quality evidence. Case presentation: A 26-year-old woman presented with progressively worsening anal pain, constipation, and hematochezia for approximately two years. Following the diagnosis of locally advanced rectal cancer (cT3N0-1M0), she received neoadjuvant chemotherapy with modified FOLFOX6 regimen and underwent laparoscopic abdominoperineal resection. Metastases to the breast and vulva developed during postoperative chemotherapy. Genetic testing revealed RAS/BRAF wild-type and microsatellite instability (MSI)-low status. Though sequential administration of irinotecan plus tegafur and tegafur plus raltitrexed-based chemotherapy in combination with bevacizumab, the disease progressed rapidly. Sadly, the patient passed away 15 months after initial diagnosis due to rapidly progressive disease. Conclusion: Rectal SRCC is associated with younger on-set, aggressive behaviors, and worse survival outcomes. Due to poor cohesiveness, SRCC tends to develop metastases. A patient’s medical history and immunohistochemical staining (such as CK20, CK7, and CDX-2) can aid in identifying the tumor origin of breast and vulvar metastases. Mutations and signaling pathways predominant in the tumorigenesis of SRCC remains unveiled. There is poor effect of conventional chemotherapies, targeted and immunotherapies for colorectal adenocarcinoma on SRCC, so novel therapies are needed to treat this patient population.